2006
DOI: 10.1002/dvdy.20986
|View full text |Cite
|
Sign up to set email alerts
|

Three types of cilia including a novel 9+4 axoneme on the notochordal plate of the rabbit embryo

Abstract: Motile monocilia play a pivotal role in left-right axis determination in mouse and zebrafish embryos. Cilia with 9؉0 axonemes localize to the distal indentation of the mouse egg cylinder ("node"), while Kupffer's vesicle cilia in zebrafish show 9؉2 arrangements. Here we studied cilia in a prototype mammalian embryo, the rabbit, which develops via a flat blastodisc. Transcription of ciliary marker genes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 60 publications
4
64
0
Order By: Relevance
“…3E-K). This expression pattern might correspond to that described in rabbits where foxj1 is expressed in the notochordal plate as the cells migrate from Hensen's node anteriorly, and eventually is expressed in the notochord (Feistel and Blum, 2006). However, in zebrafish, foxj1 expression was not detected in the notochord but in the floor plate as visualized by DIC optics (not shown) and by double in situ staining with ntl as a notochord marker (Fig.…”
Section: Expression Of Foxj1 During Zebrafish Embryogenesissupporting
confidence: 82%
See 1 more Smart Citation
“…3E-K). This expression pattern might correspond to that described in rabbits where foxj1 is expressed in the notochordal plate as the cells migrate from Hensen's node anteriorly, and eventually is expressed in the notochord (Feistel and Blum, 2006). However, in zebrafish, foxj1 expression was not detected in the notochord but in the floor plate as visualized by DIC optics (not shown) and by double in situ staining with ntl as a notochord marker (Fig.…”
Section: Expression Of Foxj1 During Zebrafish Embryogenesissupporting
confidence: 82%
“…In other organs, sensory cilia with a 9+0 microtubule pattern, such as those on olfactory neuroepithelial cells, were still present. Foxj1 is expressed in the ciliated cells of Hensen's node in the chick, and is required for left/right asymmetry determination (Blatt et al, 1999;Chen et al, 1998;Feistel and Blum, 2006;Maiti et al, 2000;Tamakoshi et al, 2006;Zhang et al, 2004). However analysis of the node in Foxj1 null mice revealed that, in contrast to the absence of airway cilia, node cilia were present.…”
Section: Abstract: Foxj1 Foxj12 Dorsal Forerunner Cell Kupffer'smentioning
confidence: 99%
“…6,39 These cilia were originally reported to display 9+0 axonemes, 8 but nodal cilia with a 9+2 and even 9+4 axonemal structures have also been found in mouse, rabbit, 40,41 and zebrafish. 42 Thus, motile as well as nonmotile cilia with variable architecture of axonemal microtubules are present in multiple tissues and organs throughout the body where they regulate key events during development and in the adult.…”
Section: Tetralogy Of Fallot Tofmentioning
confidence: 98%
“…It will be rewarding to investigate cilia in amphioxus. The prediction based on vertebrate LR cilia would be to find motile cilia that are ∼5 µm long, polarized to the posterior pole and perhaps exhibit a mix of different axoneme types, such as the 9+0, 9+2 and 9+4 configurations described in both rabbit and mouse (Caspary et al, 2007;Feistel and Blum, 2006).…”
Section: Lessons From Amphioxusmentioning
confidence: 99%
“…We have previously shown that Foxj1 mRNA is expressed in the Hensen's node of pig (Gros et al, 2009). The pig, like chick, lacks cilia at the posterior notochord, which otherwise resembles the ciliated LRO of the rabbit (Feistel and Blum, 2006). Foxj1 expression in the chick embryo has not yet been published; however, the chick Hensen's node does express the dynein heavy chain gene Dnah11 (previously known as left-right dynein, lrd) (Essner et al, 2002), which is induced by Foxj1 (Stubbs et al, 2008) and is required for the motility of LRO cilia (Supp et al, 1997).…”
Section: Lr Patterning During Vertebrate Evolutionmentioning
confidence: 99%